Arquitetura holística de redes 6G: integração das camadas de comunicação espacial, aérea, terrestre, marinha e submarina com gêmeos digitais e inteligência artificial - Araújo, Antonia Vanessa Dias (2024)
This dissertation proposes a holistic architecture for 6G networks, aiming at the integration of space, aerial, terrestrial, maritime, and submarine communication networks, targeting global and continuous connectivity. The integration of these networks, especially non-terrestrial networks (NTN), with terrestrial infrastructure presents significant technical and architectural challenges. The study focuses on modeling a unified architecture that fosters interaction between these network layers, with an emphasis on extreme and ubiquitous coverage. The methodology involves a detailed analysis of technological challenges and key enablers, such as digital twins, artificial intelligence (AI), and network orchestration, which facilitate the integration and efficient operation of 6G networks. The proposal is evaluated through simulations, highlighting the synergy between the different network components and their ability to provide ubiquitous and transparent communication to the user. It concludes that the proposed architecture provides a promising foundation for the implementation of innovative use cases, such as emergency communications, environmental monitoring, telemedicine, and smart agriculture, emphasizing the importance of extreme global coverage as one of the architectural cornerstones.